Company in Distress? : Directors Needn't Be--Mitigating Risks at the Board - Rechden, Claudio N. (International Finance Corporation, Washington, DC, 2015)
Investors see value in nominating members to the boards of companies they have invested in. Through board members, they can help improve the company's operations, define corporate strategy, adjust inefficiencies, improve governance, and ultimately increase the expected return on their investment. The authors examine the shift in the relative position of stakeholders when a company enters the penumbra of insolvency. In good times, directors rightly think of the shareholders as the parties to whom their duties to the company (and legal responsibilities) most directly extend. But once the enterprise s very survival as a going concern comes into question, the profile and legal rights of creditors and other stakeholders take on greater importance. The board must be able to demonstrate that it is doing everything it can to maximize the enterprise value of the company, and hence the likelihood that the company will meet its obligations to parties with claims (on the cash flow and assets of the company) that come before the residual interest of shareholders. This paper lists other actions (including, importantly, documentation of all material decisions) that each director should take to reduce the chances and consequences of subsequent litigation. The authors rightly emphasize the importance of securing reliable information and good-quality outside advice. For the board of a company in distress to be effective and to demonstrate that it has satisfied the duty of care, it is necessary to review the existing flow of information between management and the board and to make any changes needed to ensure that people and processes are in place for the board to receive timely and accurate information.